¿Cuánto fuego hay detrás del humo?: la impronta societaria en torno a la regulación sobre asociaciones sin fines de lucro - Bermúdez Medina, Ramón Mariano (2024)
Through this paperwork, we explore the current development of nonprofit entities as a social phenomenon and highlighting their economic relevance within national productive and competitive activity. However, its legal organization both internal and external emerges as a fundamental piece of its evolution and role, which in many cases replicates several institutions and legal principles from the business corporation model to come together in an efficient consolidated mechanism whose objective provides practicality. the execution of their ordinary activities and social purposes without this implying that both figures maintain a similar nature.The role that nonprofit entities achieve today especially union corporation privileges the development of economic activities and the promotion of interrelation with the government, which is why we must give them the prominence and real importance that they represent.